Combined oxidative and non-oxidative dehydrogenation of n-butane over VOX species supported on HMS - Setnička, Michal; Čičmanec, Pavel; Tvarůžková, Eva; Bulánek, Roman (Springer, 2013)
The combination of oxidative and non-oxidative dehydrogenation of n-butane as an attractive possibility for production of C4 olefins was studied over VOX based catalyst. Long-term activity and selectivity to desired products could be achieved over the catalysts with well dispersed monomeric vanadium oxide species supported on mesoporous silica support.
Kombinovaná oxidativní a ne-oxidativní dehydrogenace n-butanu pomocí VOX částic nanesených na HMS
Keywords: vanadium oxide; oxidative dehydrogenation; lean-oxygen conditions; n-butane; hexagonal mesoporous silica; oxid vanadu; oxidativní dehydrogenace; n-butan; hexagonální mezoporézní silika